Can massive communities of teachers facilitate collaborative reflection? Fractal design as a possible answer. Issue 1 (1st January 2017) - Clarà, Marc; Kelly, Nick; Mauri, Teresa; Danaher, P. A.
ABSTRACT: This paper explores the possibility that virtual communities of teachers with large numbers of members (referred to as massive communities of teachers ) can offer support to novice teachers by means of collaborative reflection. The paper examines and conceptualises some problems found in professional massive communities and proposes that massification can dilute what some authors have called social presence or engagement . It is argued that this dilution, among other problems, very much hinders collaborative reflection among members of the community. Collaborative reflection is argued to be a crucial part of the support that novice teachers need in their first years in the profession. Therefore, a challenge is envisioned for massive communities of teachers to avoid the dilution of social presence or engagement. The authors argue that this dilution can be overcome by the use of multiple layers within a platform, referred to as fractal design .